Psychological capital: a person-centered approach - Couture, Kelsey Len (Kansas State University, 2019)
Psychological capital is an individual’s positive psychological state of development consisting of hope, self-efficacy, optimism, and resilience. Previous research has focused on variable-centered approaches to studying PsyCap, where individual variation amongst the dimensions is aggregated, and differences between people are not given much attention. This study sought to fill that gap by utilizing Latent Profile Analysis, a person-centered approach. This seeks to find response patterns in the data, and then groups individuals who responded similarly throughout the measure into the same profile. The results of the study revealed four profiles with quantitative differences. No varying levels of these dimensions were present, the profiles all had roughly the same dimensional scores, varying from medium to high levels of PsyCap. Job demands and resources, as well as employee age, provided a means to predict which employees would be in each profile. This knowledge is a strong first step in understanding what profiles might be emerging in organizations, and why.
Keywords: Psychological capital; Job demands-resources; Latent profile analysis; Person-centered